UPAYA MANUVER ISRAEL DI AMERIKA LATIN - Muhammad Fauzan Alamari (UIN ALAUDDIN MAKASSAR, 2022)
Israel positions in the development of world met a position where Israel is hardly to make a move, fact that Israel’s economy is very strong in the Middle East region made it hard for Israel to export and distribute their porduk. At the same time, Israel need receognition from other states so Israel could get legitimation in Intenational stage. Latin America has been chososen by Israel with a special goal because there is no major sentiment by majority religion about how Israel’s born process. Despite comparing to Asia’s with their religion and history. Therefore, one question showed up on how’s Israel effort on gaining support from Latin Americas’ states? This research using qualitative method by using literature review, documentation, observation and focus group discussion as data gathering technique method. By using two level games as theory so it could create a helicopter view covering all sides and aspects of Israel maneuvers in Latin America.